2022
DOI: 10.1111/cag.12744
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of young and older adults’ attitudes and preferences towards different travel modes and residential characteristics: A study in Hamilton, Ontario

Abstract: Using Hamilton, Ontario as a case study, this study explores the difference between young (18–34 years) and older (65 + years) adults’ automobility behaviour (whether their most common mode of transportation was auto or not), by comparing their attitudes and preferences towards different travel modes. The study also investigates the differences in these two cohorts' attitudes and preferences towards residential characteristics since they can potentially impact travel behaviour. Exploratory analysis suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Additionally, the two respondents' age-groups, as defined for the study, did not exhibit significant difference in the way they relate to their neighborhoods' spatial qualities. If this evidence is valid, then it contrasts with research in other parts of the world where a distinction is made between youths and young adults, e.g., [53]. However, this finding needs to be qualified.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, the two respondents' age-groups, as defined for the study, did not exhibit significant difference in the way they relate to their neighborhoods' spatial qualities. If this evidence is valid, then it contrasts with research in other parts of the world where a distinction is made between youths and young adults, e.g., [53]. However, this finding needs to be qualified.…”
Section: Discussionmentioning
confidence: 79%
“…More details of the survey, sampling strategy, sample representativeness, information collected, and correlations between different attitudinal statements and the demographic cohorts are available in studies by Jamal et al. (2022, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Studies identified two main reasons for that. First, the unavailability of attitudes, perceptions, and preference‐related data in traditional household travel surveys (Jamal et al., 2022; Kuppam et al., 1999; Ton et al., 2020). Second, difficulties in forecasting these variables compared to sociodemographic and trip attribute data, especially in terms of establishing a causal relationship between attitudinal variables and travel behavior (Kroesen & Chorus, 2018; Kroesen et al., 2017).…”
Section: Why Is An Attitude‐based Typology Of Daily Travelers Needed?mentioning
confidence: 99%
See 1 more Smart Citation